AKUISISI KOLEKSI FIKSI PADA POJOK FIKSIPERPUSTAKAAN SMA NEGERI 1 YOGYAKARTA - Nurwidianto Yuli Saputra (Central Library of Universitas Sebelas Maret, 2019)
Fiction Corner was an interesting corner in Library of Senior High School 1 Yogyakarta. The Fiction Corner contains special collections of fiction that are not found in other libraries, especially school libraries. In addition, the level of loan collections in the fiction corner is also the most prominent compared to other collections. The acquisition in this fiction corner is unique because it is based on needs in the corner of fiction with certain considerations and stages. The purpose of this paper is to know the implementation, obstacles, and the impact of the acquisition of a collection of fiction in the fiction corner. Qualitative research methods and approaches, with field observation techniques, direct interviews and collecting available data. The results of the acquisition research are going well but there are some obstacles. Positive impact in the form of; a) increase the level of library visits; b) Increase reading interest in supporting the school literacy movement; c) Become a distinctive feature of the library; d) Increase the percentage comparison of collections of fiction and non-fiction. While the negative impacts are: a) The fiction corner is very full of users; b) Collection of fiction in the corner of fiction is not well organized; c) High loss rates